ROLE OF PROFESSIONAL ETHICS IN MAINTAINING NOTARY INTEGRITY IN INDONESIA: A PERSPECTIVE OF THEORY AND PRACTICE - Sapriana, Bela; Nurwandri, Andri; Arofi, Joe; Diana, Triwi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to examine the role of professional ethics in maintaining the integrity of notaries in Indonesia, by adopting a theoretical and practical perspective. Notaries as public officials who have the authority to make authentic deeds play an important role in the legal system in Indonesia. This research method is qualitative descriptive. This study analyzes how professional ethics can function as a moral and legal guideline for notaries, and how the application of ethical principles can reduce the potential for violations that are detrimental to society and the state. The results of the study provide insight into the importance of ethics education for notaries, supervision from authorized institutions, and enforcement of codes of ethics in maintaining the integrity of the notary profession in Indonesia. The results of the study indicate that strengthening professional ethics can improve the quality of notary services, while strengthening public trust in this profession.